The Effect of Science, Environment, Technology, and Society (SETS) Learning Model on Students' Motivation and Learning Outcomes in Biology - Sukarman Hadi Jaya Putra (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
The study aims to know the effect of the Science, Environment, Technology, and Society (SETS) learning model on students’ motivation and learning outcome on the concept of environmental change and conservation. The method used in this study is quasi-experimental with a non-equivalent control design. The sample is the tenth grade of MIA 3 and MIA 1 respectively as experiment and control group, chosen by purposive sampling technique. The instrument in this study was a questionnaire to measure motivation and a multiple-choice test to measure student learning outcomes. The data were analyzed using a t-test. The analysis results show an effect of the SETS learning model on students' motivation and learning outcomes in biology on the concept of environmental change and conservation in the tenth grade of St. John Paul II Catholic Senior High School Maumere.